2021
DOI: 10.1063/5.0068670
|View full text |Cite
|
Sign up to set email alerts
|

Surface dipole assisted charge carrier extraction in inverted architecture perovskite solar cells

Abstract: Engineering the energetics of perovskite solar cells through the introduction of surface dipoles that assist with charge carrier extraction is a promising route to enhance the device performance without altering other device layers or fabrication parameters. In this work, we introduce four different derivatives of dicationic phosphonium-bridged ladder stilbenes (PYMC) in inverted perovskite solar cells with the device structure of ITO/Meo-2pacz/perovskite/PYMC/phenyl-C61-butyric acid methyl ester (PCBM)/bathoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The slower component is ~ 200 ps for the control (0 wt%) and 2 wt% films, but it slows down to ~ 450 ps in the optimal performance film with 5 wt% PEO and is even slower (> 500 ps) in phase-segregated film (10 wt%). Through its interaction with the uncoordinated ionic species in the perovskite film, PEO can induce surface dipole formation or cause band bending between the bulk and surface of the perovskite films which will influence their electronic structure and the dynamics of charge carriers 46 , 47 .…”
Section: Resultsmentioning
confidence: 99%
“…The slower component is ~ 200 ps for the control (0 wt%) and 2 wt% films, but it slows down to ~ 450 ps in the optimal performance film with 5 wt% PEO and is even slower (> 500 ps) in phase-segregated film (10 wt%). Through its interaction with the uncoordinated ionic species in the perovskite film, PEO can induce surface dipole formation or cause band bending between the bulk and surface of the perovskite films which will influence their electronic structure and the dynamics of charge carriers 46 , 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Wong et al demonstrated that the dipolar interlayer with the energy level aligned well with those of perovskite and ETL could lead to an enhanced interface charge extraction and an improved device performance, while the dipolar interlayer that caused a mismatch in the interface energy alignment could increase the charge recombination and decrease the device performance. [ 96 ] 3‐phenyl‐2‐propen‐1‐amine (PPEA) is a conjugated aniline that presents a quasicoplanar configuration and distinct electron delocalization characteristic. PPEA molecule could anchor to the surface of the perovskite film via incorporation of amino group with uncoordinated PbX bonds and display a certain orientation on the surface of perovskite film due to strong rigidity and high steric hindrance (Figure 10c), [ 97 ] leading to the formation of a dipolar layer.…”
Section: Dipolar Interlayer In Inverted (Pin) Structured Pscsmentioning
confidence: 99%
“…[11,12] These loss mechanisms have motivated the development of a vast array of surface modification strategies. These include, for example, the treatment of the perovskite surface with a passivating agent, [5,13] mechanical polishing of the perovskite surface, [8,14] modification of the surface energetics, [15,16] formation of a low dimensional (LD) perovskite layer [17] and many others. [17,18] Among these strategies, the formation of LD/3D heterostructures is a particularly powerful approach, since it not only makes it possible to passivate point defects, but also reconstruct the 3D perovskite surface by eliminating unwanted surface crystal phases and modifying morphological defects such as pinholes and cracks.…”
Section: Introductionmentioning
confidence: 99%